Sem lenço e sem documento: a ausência de nomes no conto Os sobreviventes, de Caio Fernando Abreu, e na música Alegria, alegria, de Caetano Veloso - Marschal Ramos, Juliana; Farias Machado, Bruna; Ferreira Pavani, Cinara (Revista Leitura, 2019)
Esta pesquisa tem como objetivo analisar a ausência de nomes no conto Os sobreviventes, publicado em Morangos mofados, de Caio Fernando Abreu, e na música Alegria, Alegria, de Caetano Veloso. O cantor é mencionado na epígrafe da obra literária e por esse motivo se buscam as relações entre esses sujeitos sem nome e sem documento. Ambos são artistas que produziram suas obras durante a ditadura civil-militar que se instaurou no Brasil em 1964. Diante disso, sujeitos silenciados e angustiados por uma atmosfera de repressão são abordados na música e nas linhas do conto. As análises serão realizadas à luz das teorias de Orlandi (1995), Guimarães (2002) e Favaretto (2007). Without handkerchief or document: the absence of names in the short story Os sobreviventes, by Caio Fernando Abreu, and in the song Alegria, alegria, by Caetano Veloso This research aims to analyze the absence of names in the short story “Os sobreviventes”, published in Morangos mofados, by Caio Fernando Abreu, and in the song “Alegria, Alegria”, by Caetano Veloso. The singer is mentioned in the epigraph of the literary work and because of that we tried to find the relations between those subjects without name or document. Both of them are artists that produced their works during the civil-military dictatorship that was established in Brazil in 1964. Therefore, silenced and distressed subjects by an atmosphere of repression are represented in the lyrics of the song and the lines of the short story. The analysis will be carried out based on Orlandi (1995), Guimarães (2002) and Favaretto (2007). Keywords: Comparative literature. Music and literature. Name DOI: 10.28998/2317-9945.2019n63p260-267